Incus augmentation with glass ionomer cement in primary and revision stapes surgery - (:unkn) unknown (VENDOME GROUP LLC, 2010)
In stapedotomy, augmentation of the long process of the incus is necessary when the structure is too short or thin or when the bone has been eroded to the point that it is not possible to satisfactorily attach a piston prosthesis to it. One substance that has been used to augment the long process is glass ionomer cement (GIC). GIC is a dental bone cement that is finding new uses in otologic procedures. We conducted a retrospective study of 10 stapedotomies (6 primary and 4 revision cases) that included the use GIC to augment an insufficient long process. In all 10 cases, surgery was successful and without complication. A comparison of pre- and postoperative audiometry revealed significant improvements in mean air-conduction threshold and air-bone gap following surgery. Our findings suggest that GIC is safe and effective in augmenting the long process of the incus during both primary and revision stapedotomy.
Keywords: BONE-CEMENT; LONG PROCESS; MIDDLE-EAR; RECONSTRUCTION; STAPEDECTOMY; ATTACH